Comparative proteomic analysis provides insights into wood formation in immature xylem at different ages in Eucalyptus urophylla × Eucalyptus grandis - Liu, Guo; Zhang, Guowu; Wu, Zhihua; Lu, Wanhong; Lin, Yan; Wang, Chubiao; Shang, Xiuhua; Huang, Anying; Luo, Jianzhong (Frontiers in Plant Science, 2024)
Wood formation is a crucial developmental stage in the life cycle of a woody plant; this process has substantial scientific research implications and practical applications. However, the mechanisms underlying woody plant development, especially the process of wood formation, remain poorly understood. As eucalyptus is one of the fastest growing tree species in the world, understanding the mechanism of wood formation in eucalyptus will greatly promote the development of molecular breeding technology for forest trees. In this study, we investigated the proteomic profile of immature xylem at four different ages of E. urograndis using iTARQ technology. We identified 5236 proteins and 492 differentially abundant proteins (DAPs). The expression profiles of the DAPs corresponding to coding genes associated with wood formation were assessed using qRT-PCR. From the different expression profiles, it is inferred that the genes encoding kinesin, CDKD3, EXPA13, EXPA2, XTH27, EGases, UGT76E2, LAC, CCoAMT, CesA3, PAL, and CAD may undergo posttranscriptional regulation (PTR). Additionally, the genes encoding EIN2, ETR, MC4-like, and XCP may undergo posttranslational modifications (PTMs). In this study, we investigated changes in wood formationrelated proteins at the protein abundance level in the immature xylem of Eucalyptus urophylla × Eucalyptus grandis, thereby elucidating potential regulatory mechanisms of key proteins involved in eucalyptus wood formation. This study may provide theoretical guidance for further research on molecular breeding techniques and genetic improvement related to the cultivation of rapidly growing and high-quality trees.